ISLAMPHOBIA DAN ANTISEMITISME MODERN PADA MEDIA ONLINE JERMAN - Kartika, Ajeng Dianing (Universitas Negeri Surabaya, 2018)
Islamophobic and Antisemitism have nowadays become trending topics in Germany. The rise of muslims population in Germany during migration crisis that cause pro and contra in the society can be the main cause of the Islamophobic in the country lead by Angela Merkel. In the other side there is another phenomenon called antisemtism that historically has occurred since the Nazi?s era. Currently this phenomenon suddenly rise up during migration crisis and it has been strongly discussed after the controversy created by duo rappers Kollegah (Felix Blume) and Farid Bang (Farid El Abdellaoui) who took home the prize for their anti-semitism songs in album Jung, Brutal, Gutaussehend 3. Pro and contra appears and it becomes trending topic in German online newspaper beside the islamophobia that?s still debatable. Even though these two phenomenon has a similiarity, namely ?anxiety feeling or extreme fear of something?, there is different strategies used by the Press in Germany. Crictical analysis is needed to reveal specific strategies applied and the impact of the kind of strategies on the representation of Muslims and Jews in Germany. Based on critical discourse studies, it can be concluded that the German online newspaper define Islam as out group who create islamophobic. But, Jews are represented differently as a victim of anti-Semitism.